2006
DOI: 10.1128/jvi.80.2.964-974.2006
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus E1B 55-Kilodalton Protein Is Required for both Regulation of mRNA Export and Efficient Entry into the Late Phase of Infection in Normal Human Fibroblasts

Abstract: The human adenovirus type 5 (Ad5) E1B 55-kDa protein is required for selective nuclear export of viral late mRNAs from the nucleus and concomitant inhibition of export of cellular mRNAs in HeLa cells and some other human cell lines, but its contributions(s) to replication in normal human cells is not well understood. We have therefore examined the phenotypes exhibited by viruses carrying mutations in the E1B 55-kDa protein coding sequence in normal human fibroblast (HFFs). Ad5 replicated significantly more slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
63
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 99 publications
9
63
0
1
Order By: Relevance
“…1). The 2-to 3-order-of-magnitude decreases in yield of this null mutant observed when cells were not exposed to IFN are also consistent with the requirement for the E1B 55-kDa protein to allow maximally efficient viral DNA synthesis in HFFs (47,62). In the absence of IFN, no significant impact of the E1B Sub19 substitutions on virus yield was observed (Fig.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…1). The 2-to 3-order-of-magnitude decreases in yield of this null mutant observed when cells were not exposed to IFN are also consistent with the requirement for the E1B 55-kDa protein to allow maximally efficient viral DNA synthesis in HFFs (47,62). In the absence of IFN, no significant impact of the E1B Sub19 substitutions on virus yield was observed (Fig.…”
Section: Resultssupporting
confidence: 60%
“…As these initial observations indicated that the enhanced sensitivity of replication of this mutant to IFN is not a trivial consequence of failure to synthesize stable E1B protein, we examined the properties of this mutant in more detail. We first compared its sensitivity to IFN to that of the corresponding E1B 55-kDa protein null mutant, AdEasyE1⌬2347 (48), following infection of HFFs at a high multiplicity (50 PFU/cell) for 36 h or at a low multiplicity (3 PFU/cell) for 88 h. The former condition corresponds to a single infectious cycle with the great majority of cells initially infected (62). In contrast, the low-multiplicity protocol allowed spread of infection from the small number of cells initially infected and is therefore likely to be more representative of infection and the impact of host antiviral defenses in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore initiated investigations of the roles played by the E1B 55-kDa protein during Ad5 replication in normal human cells. One unexpected observation was that, in the absence of this protein, viral DNA synthesis was impaired in proliferating human fibroblasts (32), although it is not in HeLa and other lines of transformed human cells (5,34,38,66,100). Furthermore, McCormick and colleagues had previously reported that no differences in viral DNA synthesis were observed in quiescent small airway epithelial cells infected by wild-type virus or the E1B 55-kDa null mutant ONYX-015 (also known as dl1520) (63).…”
mentioning
confidence: 99%
“…To assess the effect, if any, of the E4 Orf3 protein on p53 stabilization and accumulation, HFFs were infected with the E1B 55-kDa-null mutant and the ⌬E1B/⌬EOrf3 double mutant for increasing periods, and p53 was examined by immunoblotting, as described in Materials and Methods. By 24 h after infection, the initial period of the late phase in these cells (102), p53 was readily detected in cells infected by the mutant viruses, but not in cells infected by the phenotypically wild-type parent of ⌬E1B, AdEasyE1 ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%